BAHAN AJAR DALAM PEMBELAJARAN TEKS SASTRA DRAMA DI KELAS XI SMA NEGERI 4 SINGARAJA - Ni Made Novia Lestari; I Nyoman Yasa; I Putu Mas Dewantara (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2021)
This study aims to describe (1) The types of teaching materials in learning drama literary texts in class XI SMA Negeri 4 Singaraja, (2) The procedure for using teaching materials in learning drama literary texts, (3) Evaluation of teaching materials in text learning drama literature. This study used a qualitative descriptive method. The subject of this research is one teacher who teach drama in class XI SMA Negeri 4 Singaraja. The data collection method used are observation, interview, and documentation. The results of this study are (1) The types of teaching materials used by teachers in learning drama literary texts, namely, Videos on Youtube, Materials in Google Classroom, Materials on the Web, and Learning Videos. (2) The procedure for using teaching materials in learning drama literary texts which includes three stages of procedures, Providing the basic concepts of drama through videos on YouTube, Presenting modules to check student understanding, and Presenting a summary of the material and learning videos. (3) Evaluation of teaching materials in learning drama literary texts, namely, Adapting to KD, Characteristics of students, and Authentic and interesting. From the results obtained, it can be concluded that the use of teaching materials for literary drama texts in class XI of SMA Negeri 4 Singaraja has been carried out very well. Keywords: teaching materials; drama; literary text